Modelling and Simulation of Floor Cleaning Machine - Dr. Ravi Kumar Panthangi, Dr. K. Srinivasa Rao, Merugu Akhil, Balla Akhil (International Journal of Advanced Science and Technology, 2020)
Cleaning the surroundings is the basic need for all human beings and it is necessary for daily routine processes. Cleaning is difficult for humans where more traffic is present. The aim of this study is to model and simulate floor cleaning machine. The purpose of this study is to analyze whether the model of floor cleaning machine will sustain the load and work normally. This machine consists of Frame, mop, motor, battery, water tank and pipes. According to the application, the size of the machine varies. Fusion 360 software is used to model and analyze the elements of floor cleaning machine and its assembly